Building effective recommender systems for tourists. Issue 2 (16th June 2022) - Massimo, David; Ricci, Francesco
Abstract: Recommender systems (RSs) are personalized information search and discovery applications helping users to identify and choose useful items and information. In this paper, we focus on the tourism application scenario and its specific requirements. We discuss a novel RS approach that copes with the specific application constraints of the domain and produces recommendations that better match the true needs of tourists. We illustrate the proposed next POI recommendation approach in a case study and we compare it with a state‐of‐the‐art nearest neighbor‐based next item RS. With the analysis of this case study, we aim at illustrating the specific features of the compared approaches also with the goal to raise the discussion on RSs validation methods, with a particular attention to tourism applications. We finally discuss some significant limitations of current evaluation approaches that must be addressed in future studies.